Effects of magnesium silicate (talc) on feed flow characteristics and growth performance, carcass characteristics, and stomach morphology in finishing pigs - S P Sorrell; S L Traylor; S L Johnston; I H Kim; Robert H Hines; G A Kennedy; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1998)
Talc did not affect growth performance, carcass characteristics, or stomach ulceration in finishing pigs. Feeder bridging scores and coefficients of static force (the force needed to result in particle movement) were increased with added talc, both of which indicate reduced feed flowability. In a second experiment, reducing particle size from 1,050 microns to 450 microns increased the coefficients of static force, dynamic force, and angle of repose. Adding talc to either particle size diet did not improve feed flow characteristics.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Talc; Ulcers; Bridging; Finishing pigs